IMPLEMENTASI PERATURAN DAERAH KOTA PEKANBARU NO.3 TAHUN 2002 TENTANG HIBURAN UMUM (STUDI KASUS TAMAN REKREASI ALAM MAYANG KOTA PEKANBARU) - Winda Yulianti Masril; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Pekanbaru city is that the city will be minimal, especially tourism, nature tourism, and in spatial areas already rung can be used as a place of tourism. Goverment Pekanbaru indeed less able to manage the tourist area and to achieve the tourist destination ahead does the government involves a third person in the management, one of which is a recreational park Alam Mayang in Pekanbaru, Recreation Alam Mayang is one of the natural attractions in the city of Pekanbaru in is owned by the private sector, and has a strategic location not far from downtown, but there are some issues that are not in accordance with local regulations in force in the city of Pekanbaru, one of which is abuse Recreation place this as a place sordid causing unrest of visitors and local residents and the lack of facilities available at this recreation area.To analyze these problems the author uses the theory of Van Meter Van Horn which in accordance with these problems, Standard's policy objectives, resources, communication between organizations, implementing characteristics, economic and political environment. This research is a descriptive study with qualitative approach, where data collection techniques are observation and interviews with key informants as key informants.It can be concluded that the implementation of Pekanbaru City Regional Regulation 3 of 2002 on public entertainment (Case Study Recreation Park Alam Mayang In Pekanbaru City) have some problems so that this implementation is not effective because of the constraints faced by internally from them.Keywords: Implementation, Department of Culture and Tourism, Recreation Alam Mayang